The role of commitment amongst tourists and intelligent virtual assistants - Loureiro, S. M. C.; Bilro, R. G. (Journal of Promotion Management, 2022)
This paper aims to analyze Attachment and Emotional Values as antecedents of Commitment to intelligent virtual assistants (IVA) and Commitment as a driver of Loyalty Intentions toward the IVA. Data is collected from a sample of 124 active users of IVA systems in tourism settings by the mean of an online survey. The findings contribute to the existing literature by revealing that Attachment and Emotional Values positively influence tourists Commitment to Intelligent Virtual Assistants. Moreover, findings reveal that Commitment positively influences Loyalty Intentions. This study is a first attempt to analyzing the commitment process between users (i.e., tourists) and artificial intelligent systems (i.e., intelligent virtual assistants).